Ketepatan Penggunaan Metotreksat pada Pasien Reumatoid Artritis di Rumah Sakit Emanuel Klampok berdasarkan Kriteria Eksplisit - Rizki Puspitasari; Tunggul A. Purwonugroho; Hanif N. Baroroh (Indonesian Journal of Clinical Pharmacy, 2014)
Metotreksat (MTX) adalah agen antiinflamasi dan imunosupresan yang menjadi lini pertama terapi reumatoid artritis (RA). Penelitian ini bertujuan mengevaluasi penggunaan MTX pada pasien RA di Rumah Sakit Emanuel Klampok berdasarkan kriteria indikasi, indikator proses, komplikasi, dan indikator hasil. Analisis data dilakukan secara deskriptif evaluatif menggunakan data rekam medik13 pasien rawat inap dan 27 pasien rawat jalan. Hasil penelitian menunjukkan ketepatan indikasi 100%. Pasien dengan faktor risiko gangguan GI, hepatotoksik, dan toksisitas bone marrow berturut-turut 35 pasien, 19 pasien, dan 15 pasien. Pemberian MTX dengan dosis tepat sejumlah 32 pasien, dosis tidak tepat dengan ClCr 61–80 mL/menit sejumlah 3 pasien, ClCr 51–60 mL/menit sejumlah 2 pasien, ClCr 10–50 mL/menit sejumlah 1 pasien, dan SGPT >3 nilai normal sejumlah 2 pasien. Interaksi MTX dengan NSAID sejumlah 35 pasien dan dengan agen hepatotoksik sejumlah 19 pasien. Komplikasi terjadi pada 7 pasien berupa gangguan GI dan 1 pasien berupa sirosis. Indikator hasil berupa berkurangnya keluhan klinis seperti nyeri dan kakuterjadi pada 10 pasien dan pasien yang membaik sejumlah 2 pasien. Indikasi penggunaan MTX telah sesuai dengan kriteria sedangkan indikator proses, komplikasi, dan indikator hasil masih belum sesuai.Kata kunci: Metotreksat, reumatoid artritis, Rumah Sakit Emanuel KlampokAccuracy of Methotrexate Use in Rheumatoid Arthritis Patients in Emanuel Klampok Hospital based on Explicit CriteriaMethotrexate (MTX) is the first line therapy for rheumatoid arthritis (RA) as an antiinflammatory and immunosuppressant agent. The purpose of this study was to evaluate the use of MTX in patients with RA at Emanuel Klampok Hospital based on criteria that include indication, process indicators, complication, and outcome indicators. The medical record from 13 inpatients and 27 outpatients who used MTX were compared with the criteria. The results of this study suggested that all of the patients had appropriately indications to use MTX. Patients with risk factors that lead to GI disorders, hepatotoxicity, and bone marrow toxicity were 35 patients, 19 patients, and 15 patients, respectively. There were 32 patients used MTX with the correct dosage, meanwhile incorrect dosage was showed in 3 patients with ClCr 61–80 mL/minute, 2 patients with ClCr 51–60 mL/minute, 1 patient with ClCr 10–50 mL/minute, and 2 patients with SGPT >3 normal value. The interaction with NSAID was detected in 35 patients and the interaction with hepatotoxicity agents in 19 patients. Complication occurred in 7 patients with effects that occur were GI disorders and 1 patient with chirrosis. There were 10 patients with clinical complaints reduced and 2 patients with the better condition. This study suggested that in Emanuel Klampok Hospital, MTX was appropriately use regarding to indication, however, it still not appropriate regarding to process indicators, complication, and outcome indicators.Key words: Emanuel Klampok Hospital, methotrexate, rheumatoid arthritis